Index of Academic Freedom in Ukraine and in the World: Conceptual Approaches and Comparative Dynamics - Zaiets, S. V. (Statistics of Ukraine, 2024)
The article analyzes and systematizes different approaches to understanding the concept of “academic freedom”, which is identified with freedom of speech, freedom of research and freedom of teaching in an academic environment. Google Trends analytics over the past 5 years confirm constant interest in the problem of academic freedom in the world and sporadic interest in Ukraine. The number of domestic scientific and pedagogical works in Google Scholar (without citation) on the topic of academic freedom has been determined. It is shown that academic freedom is in danger in Europe and abroad. Selected sources of data on the violation of academic freedom in the university sector, the monitoring of which will help reveal harsh repressions, as well as various forms of soft repressions. The relevance of developing a comprehensive approach to the concept of academic freedom and combating potential threats to it is substantiated. Analyzed in dynamics for 1990–2023. and the regional section (Western Europe, North America, Ukraine) index of academic freedom, proposed by German and Swedish researchers, and its components: freedom of research and teaching; freedom of academic exchange and distribution; institutional autonomy of universities; campus integrity; freedom of academic and cultural self-expression. The methods used to increase the validity, reliability and comparability of the index of academic freedom are considered. Attention is focused on the strengths of the index of academic freedom, which provides comparative data for each country for a certain time and on a global scale, records important periods in the history of countries, points to recent alarming events that should be perceived as important warning signs reflecting the current climate in the country. Among the shortcomings of the index, its focus only on global comparison, the lack of the possibility of specifying fluctuations in academic freedom within the country are highlighted. It is determined that in the whole world there is a slight drop in global levels of all indicators of academic freedom, however, there is a significant threat of a drop in academic freedom in individual countries. The need to use the index of academic freedom and its indicators in the activities of domestic institutions and governing bodies of higher education is substantiated. It is recommended to use the index of academic freedom as a basis for regular assessment, dialogue and reforms in the field of higher education.